Mechanistic Studies on the Roles of the Oxidant and Hydrogen Bonding in Determining the Selectivity in Alkene Oxidation in the Presence of Molybdenum Catalysts. Issue 6 (4th January 2013) - Chandra, Prakash; Pandhare, Swati L.; Umbarkar, Shubhangi B.; Dongare, Mohan K.; Vanka, Kumar
Abstract When the molybdenum oxo(peroxo) acetylide complex [CpMo(OO)(O)CCPh] is used as a catalyst for the oxidation of olefins, completely different product selectivity is obtained depending on the oxidant employed. When tert‐butyl hydroperoxide (TBHP, 5.5 M) in dodecane is used as the oxidant for the oxidation of cyclohexene, cyclohexene oxide is formed with high selectivity. However, when H2O2 is used as the oxidant, the corresponding cis‐1, 2‐diol is formed as the major product. Calculations performed by using density functional theory revealed the nature of the different competing mechanisms operating during the catalysis process and also provided an insight into the influence of the oxidant and hydrogen bonding on the catalysis process. The mechanistic investigations can therefore serve as a guide in the design of molybdenum‐based catalysts for the oxidation of olefins.